Characteristics of Epilepsy Outpatients Sufferer at Bali Mandara Hospital in January - December 2019 - Saraswati, Putu Dewinadya (E-Jurnal Medika Udayana; Vol 11 No 1 (2022): E-Jurnal Medika Udayana, 2022)
Background: Epilepsy is one of the chronic neurologic disease that often found the cases. Epilepsy is a global health issue that affected 50 million people around the world Objective: This study aims to determine the characteristics of epilepsy outpatients in Bali Mandara Regional Hospital in January-December 2019. Method: The method used in this study was a cross sectional descriptive study using secondary data of patient medical records. Obtained data that met the inclusion criteria was 149. Data analyzed by using SPSS 20 program. Results: The most frequent age category is 0-17 years about 57%, more often in male about 51%, dominant etiology is idiopathic about 65,8%, the most common type of seizure was generalize about 69.8%, anti-epileptic drugs that frequently used was carried out in the form of monotherapy about 50,3%. Conclusion: The most common age category is 0-17 years, male slightly more than female, idiopathic epilepsy is more frequently happened, most common type of seizure was generalized, monotherapy and polytherapy anti-epileptic drugs is almost the same but primarily in the form of monotherapy is the most received by the patients Keywords : epilepsy, characteristics, anti epileptic drug